Answer:
x= 2
y = 20
Step-by-step explanation:
y = 6x + 8
y = –4x – 2
y = 4 (6x + 8
)
y = 6 (–4x – 2)
y = 24x + 32
y = –24 -12
___________
y = 20
input that back into the equation to find x
20 = 6x + 8
20 - 8 = 6x
12 = 6x
x= 2
Answer:
Step-by-step explanation:
Mistakes: The student did not distribute the 3 into 2, and the student did not distribute the 6 into negative 2. The student also left out the negative 2x in the first half of the equation.
Answer:
![y \in R; y \neq 0](https://tex.z-dn.net/?f=y%20%5Cin%20R%3B%20y%20%5Cneq%200)
Explanation: For this, it is often best to find the horizontal asymptote, and then take limits as x approaches the vertical asymptote and the end behaviours.
Well, we know there will be a horizontal asymptote at y = 0, because as x approaches infinite and negative infinite, the graph will shrink down closer and closer to 0, but never touch it. We call this a horizontal asymptote.
So we know that there is a restriction on the y-axis.
Now, since we know the end behaviours, let's find the asymptotic behaviours.
As x approaches the asymptote of 7⁻, then y would be diverging out to negative infinite.
As x approaches the asymptote at 7⁺, then y would be diverging out to negative infinite.
So, our range would be:
Answer:
adasdasdadsads
Step-by-step explanation:
Answer:
1/1080
1/3
y=cos(x/3)
Step-by-step explanation:
just did it